The physiological effect of 800 mcg and 1600 mcg inhaled salbutamol during a football specific treadmill run at high ambient temperatures. Issue 15 (10th November 2011) - Dickinson, J; Hu, J; Chester, N; Drust, B; Whyte, G; Loosemore, M
Abstract : The World Anti-doping Agency stipulates that athletes who declare salbutamol use should not exceed 1600 μg over a 24 h period. No studies have investigated the physiological effect of 1600 μg of inhaled salbutamol on intermittent sports. This study investigated the physiological effect of inhaling 800 μg and 1600 μg of salbutamol prior to a football specific run at high ambient temperatures. Five male non-asthmatic football players (mean+SD; age 24+4 y; weight 71+4 kg; height 175+5 cm) volunteered. Participants attended the lab on three occasions to inhale either a placebo (PLA), 800 μg of salbutamol (800SAL) or 1600 μg of salbutamol (1600SAL) 15 min prior to performing a football-specific run for 45 min at 30°C. The football specific run consisted of seven stages which included two high intensity stages and five low intensity stages. During each stage VO2, RER, HR and blood lactate was measured. Repeated measures ANOVA were performed to investigate the changes in VO2, RER, HR and blood lactate during each stage. Significance was assumed if p<0.05. During stage one and two HR was higher (p=0.010; p=0.013) in 800SAL (143.3+10.3 b.min -1 ; 148.0+12.2 b.min -1 ) and 1600SAL (141.6+2.5 b.min -1 ; 147.0+4.0 b.min -1 ) when compared to PLA (119.3+11.9 b.min -1 ; 129.3+9.6 b.min -1 ). Following stage two blood lactate was higher (p=0.020) in 800SAL (4.2+1.8 mmol.l -1 ) and 1600SAL (4.5+1.6 mmol.l -1 ) when compared with PLA (2.4+1.2 mmol.l -1 ). Following stage five blood lactate was higher (p=0.014) in 800SAL (4.2+1.6 mmol.l -1 ) and 1600SAL (5.0+1.4 mmol.l -1 ) when compared with PLA (2.8+1.0 mmol.l -1 ). The increased HR (stages one and two) and increased blood lactate concentration (stages two and five) observed following salbutamol inhalation, suggests supratherapeutic doses of salbutamol may increase the physiological cost during a football match.